Evolutionary morphology of the rabbit skull - Kraatz, Brian; Sherratt, Emma (PeerJ, 2016)
The skull of leporids (rabbits and hares) is highly transformed, typified by pronounced arching of the dorsal skull and ventral flexion of the facial region (i.e., facial tilt). Previous studies show that locomotor behavior influences aspects of cranial shape in leporids, and here we use an extensive 3D geometric morphometrics dataset to further explore what influences leporid cranial diversity. Facial tilt angle, a trait that strongly correlates with locomotor mode, significantly predicts the cranial shape variation captured by the primary axis of cranial shape space, and describes a small proportion (13.2%) of overall cranial shape variation in the clade. However, locomotor mode does not correlate with overall cranial shape variation in the clade, because there are two district morphologies of generalist species, and saltators and cursorial species have similar morphologies. Cranial shape changes due to phyletic size change (evolutionary allometry) also describes a small proportion (12.5%) of cranial shape variation in the clade, but this is largely driven by the smallest living leporid, the pygmy rabbit (Brachylagus idahoensis). By integrating phylogenetic history with our geometric morphometric data, we show that the leporid cranium exhibits weak phylogenetic signal and substantial homoplasy. Though these results make it difficult to reconstruct what the ‘ancestral’ leporid skull looked like, the fossil records suggest that dorsal arching and facial tilt could have occurred before the origin of the crown group. Lastly, our study highlights the diversity of cranial variation in crown leporids, and highlights a need for additional phylogenetic work that includes stem (fossil) leporids and includes morphological data that captures the transformed morphology of rabbits and hares.
Keywords: Geometric morphometrics; Macroevolution; X-ray micro computed tomography; Lagomorpha; Leporidae